RADIX - Rianti, Muthia; Mansyur, Herlinda (SENDRATASIK UNP, 2019)
AbstractÂ The creation of "RADIX" Dance works aims to create creative dance works and reveal ideas inspired by the root bridge found on the south coast. The dance Works "RADIX" is inspired by the root bridge (the titular title) found in the village of Pulut-Pulut, in the district IV Nagari Bayang Utara. The plot of the "RADIX" dance interpreting the shape of the root braid into the dancer's body. What is the process of root braid on the bridge of the titular temple to become a bridge. This work of "RADIX" further illustrates how the root characteristics of the titular bridge are on the point. The properties of the roots are bending, propagating and strongly interpreted to the body of the dancer through the motion that corresponds to the root character. Dancers in the work "RADIX" should kill the character of the motion like the roots, because with the character of this dance work will be conveyed to the audience. The dance Works "RADIX" is a symbolic dance. The nature of the roots is interpreted to the body of the embodied through motion, stage, cosmetology, fashion, lighting, and emphasized by the music.Â Keywords: Radix, Radix Dance, Perform Art